Considerations about the use of Ozone therapy (O3) in the treatment of Endometriosis (Research, Society and Development, 2020)
Endometriosis is defined as the presence of an endometrial gland and / or endometrial stroma outside the uterus. Endometriosis patients have a clinical picture with a lot of variability, with the prevalence of symptomatic dysmenorrhea, dyspareunia, chronic pelvic pain, dysuria, dyschezia and infertility. Currently, it is widely accepted that endometriosis is a disease associated with a general inflammatory response in the peritoneal cavity and that oxidative stress has been proposed as a potential factor involved in the pathophysiology of the disease. In this context, it is important to search for innovative and low-cost therapeutic alternatives, capable of preventing and / or decreasing the progression of tissue damage and mitigating the impacts inherent to the disease. Thus, this study seeks, through narrative review, to provide an understanding of the current available evidence regarding the importance of ozone therapy and its possible applicability in the treatment of endometriosis. Evidence shows that ozone has the ability to improve body oxygenation, modulate the inflammatory process, increase the antioxidant and immune system, help to alleviate diseases caused by oxidative damage similar to the complications of endometriosis. Thus, the evidence found in this study indicates that ozone therapy could be proposed as an effective and safe therapeutic intervention in the treatment of endometriosis, within the integrative practices. However, there are no controlled, randomized clinical trials that have evaluated the effect of ozone therapy on the prevention, control and treatment of endometriosis.